2010
DOI: 10.1161/circulationaha.109.919456
|View full text |Cite
|
Sign up to set email alerts
|

Response to Ticagrelor in Clopidogrel Nonresponders and Responders and Effect of Switching Therapies

Abstract: Background-The antiplatelet effects of the Platelet Inhibition and Patient Outcomes (PLATO) trial dose of ticagrelor in patients nonresponsive to clopidogrel and after they switch agents are unknown. Methods and Results-Patients with stable coronary artery disease on aspirin therapy received a 300-mg clopidogrel load; nonresponders were identified by light transmittance aggregometry. In a 2-way crossover design, nonresponders (nϭ41) and responders (nϭ57) randomly received clopidogrel (600 mg/75 mg once daily) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
261
2
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(285 citation statements)
references
References 24 publications
8
261
2
14
Order By: Relevance
“…One major and three minor bleeding events occurred either during or after ticagrelor therapy, while no bleeding events were reported for patients taking clopidogrel. Only five serious adverse events (MI, hypotension, atrial fibrillation, and bradycardia) were reported during this study and they all occurred either during or after ticagrelor therapy [28]. Although switching agents might be able to significantly reduce platelet aggregation, this may not translate to a reduction in clinical outcomes such as MACE.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One major and three minor bleeding events occurred either during or after ticagrelor therapy, while no bleeding events were reported for patients taking clopidogrel. Only five serious adverse events (MI, hypotension, atrial fibrillation, and bradycardia) were reported during this study and they all occurred either during or after ticagrelor therapy [28]. Although switching agents might be able to significantly reduce platelet aggregation, this may not translate to a reduction in clinical outcomes such as MACE.…”
Section: Discussionmentioning
confidence: 89%
“…Compassionate use of prasugrel was able to be obtained for four of the patients and adequate platelet inhibition was observed in all of the patients after four weeks [27]. The RESPOND trial was a crossover designed trial in 98 patients comparing both responders and non-responders of clopidogrel to ticagrelor which is an oral reversible P2Y 12 inhibitor [28]. Ticagrelor was able to significantly inhibit more platelet aggregation than clopidogrel in non-responders (p<0.05) and platelet aggregation fell significantly when patients were switched from clopidogrel to ticagrelor (p<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Third, because clopidogrel and eptifibatide 18‐ versus 2‐hour infusion increased bleeding,8 we did not randomize patients to ticagrelor and eptifibatide 18‐ versus 2‐hour infusion. Fourth, because it has been demonstrated23 that the vasodilator‐stimulated phosphoprotein assay had minor differences as compared with the LTA measurements, we did not perform the vasodilator‐stimulated phosphoprotein assay to measure platelet reactivity index. Instead, multiple platelet function tests were performed in duplicates.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that switching patients from clopidogrel to ticagrelor result in rapid, higher and consistent IPA. 21 …”
Section: Ticagrelor: Clinical Developmentmentioning
confidence: 99%